Differential change in folk disease concepts’ - Tharp, Roland G.; Meadow, Arnold (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The hypothesis is proposed that in the Mexican-American, Anglo-American contact situation, folk-medicine beliefs do not change as an aggregate but that individual component of these beliefs will undergo modification according to the degree to which they mesh with the etiological assumptions of the superordinate culture. To test this hypothesis an interview study was conducted using as subjects 250 randomly selected Mexican-American families in Tucson, Arizona. Results indicated that explanations of diseases which are expressed by naturalistic etiological concepts are less resistant to extinction than those expressed in terms of emotional origin. The latter in turn were more persistent than diseases explained by magical etiological conceptions.